Crystal growth, perfection, linear and nonlinear optical, photoconductivity, dielectric, thermal and laser damage threshold properties of 4-methylimidazolium picrate: an interesting organic crystal for photonic and optoelectronic devices. (13th October 2016) - Rajesh, K; Arun, A; Mani, A; Kumar, P Praveen
Abstract: The 4-methylimidazolium picrate has been synthesized and characterized successfully. Single and powder x-ray diffraction studies were conducted which confirmed the crystal structure, and the value of the strain was calculated. The crystal perfection was determined by a HRXR diffractometer. The transmission spectrum exhibited a better transmittance of the crystal in the entire visible region with a lower cut-off wavelength of 209 nm. The linear absorption value was calculated by the optical limiting method. A birefringence study was also carried out. Second and third order nonlinear optical properties of the crystal were found by second harmonic generation and the z-scan technique. The crystals were also characterized by dielectric measurement and a photoconductivity analyzer to determine the dielectric property and the optical conductivity of the crystal. The laser damage threshold activity of the grown crystal was studied by a Q-switched Nd:YAG laser beam. Thermal studies established that the compound did not undergo a phase transition and was stable up to 240 °C.